2011
DOI: 10.1186/1471-2180-11-161
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Streptococcus suis isolates as determined by comparative genome hybridization

Abstract: BackgroundStreptococcus suis is a zoonotic pathogen that causes infections in young piglets. S. suis is a heterogeneous species. Thirty-three different capsular serotypes have been described, that differ in virulence between as well as within serotypes.ResultsIn this study, the correlation between gene content, serotype, phenotype and virulence among 55 S. suis strains was studied using Comparative Genome Hybridization (CGH). Clustering of CGH data divided S. suis isolates into two clusters, A and B. Cluster A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
62
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 45 publications
6
62
0
Order By: Relevance
“…G. mellenella larvae have been used to study antibiotic treatment for different bacterial and fungal infections [27, 35, 36]. To assess the utility of G. mellonella larvae to study antibacterial therapies against S. suis , we confirmed that antibiotic therapy could rescue larvae from S. suis infection.…”
Section: Resultsmentioning
confidence: 57%
See 3 more Smart Citations
“…G. mellenella larvae have been used to study antibiotic treatment for different bacterial and fungal infections [27, 35, 36]. To assess the utility of G. mellonella larvae to study antibacterial therapies against S. suis , we confirmed that antibiotic therapy could rescue larvae from S. suis infection.…”
Section: Resultsmentioning
confidence: 57%
“…The virulence of S. suis isolates (Table 1) that had been assessed for virulence in a piglet infection model [35] was assessed in G. mellonella larvae by inoculation with 20 μL of suspensions containing 1 × 10 5 to 1 × 10 8 CFU/ml and incubation at 37 °C. Notably, isolates reported as virulent in pigs (6388, 6555/NCTC 428, P1/7, 3881/S10, 7997) [35] and in a zebrafish larval model (3881/S10, 6555/NCTC 428) [26] showed dose-dependent virulence in G. mellonella larvae (Figs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, little is known of the S. suis population structure. High genetic diversity within the species adds complexity to the understanding of the clonal relationships between strains, especially low-virulence strains (5)(6)(7). In a previous study, we developed a whole-genome sequencebased typing scheme to identify and classify S. suis populations as one of seven minimum core genome (MCG) groups (8).…”
mentioning
confidence: 99%